(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the political aspects of water shortage, which is the cause and instrument of international conflicts. The growing threat of glaciers and the reduction of water flows. World practice of solving problems related to water issues and international cooperation at the level of agreements and treaties. Also the causes of international conflicts that arise between countries. The role of transboundary rivers in particular on the example of the Amu Darya and Syr Darya as some of the largest rivers in Central Asia. Additionally, the participation of Afghanistan as a user of water resources from the Amu Darya. Analysis of the international situation around water shortage with examples of some countries, such as: India, Pakistan, Mexico and others. Also reports of international organizations such as UNESCO, UN and opinions of some leaders on water issues.